Collaboration and collegiality amongst educators in high performing schools in the Western Cape - Laubscher, Susanna Maria (School of Education, 2014)
This study investigated the nature and extent of collaboration and collegiality amongst 195 high school educators in six high performing schools in the Cape Metropole, Western Cape, Cape Town. A case study approach was used and questionnaires and intervies were used as research instruments. This study found that the schools in this sample display high and widespread levels of collaboration and collegiality amongst educators. The collegial activities are fostered in a collaborative domain during regular on-site formal activities. These carefully structured formal collaborative activities provide training forums for inexperienced educators.